2014
DOI: 10.2106/jbjs.l.01041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perioperative Allogeneic and Autologous Blood Transfusion on Acute Wound Infection Following Total Knee and Total Hip Arthroplasty

Abstract: Perioperative allogeneic transfusion was associated with a higher rate of reoperations for suspected acute infection. However, patients with allogeneic exposure had increased infection risk factors. After adjustment for the total number of units transfused and an ASA score of >2, allogeneic exposure was not significantly predictive of a reoperation for infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 20 publications
5
78
1
5
Order By: Relevance
“…Previous studies have found increased risk of surgical site infection after transfusion in orthopedic surgery, 27,33,35,36 including an increased risk of reoperation for infection after receiving transfusion preoperatively for adult THA. 34 In the current study, the only association of transfusion with SSI was an increased risk of superficial infection with large volume transfusion in the NM group; this association was not significant. The rarity of SSI in pediatric surgical populations likely limits the likelihood of finding any association.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies have found increased risk of surgical site infection after transfusion in orthopedic surgery, 27,33,35,36 including an increased risk of reoperation for infection after receiving transfusion preoperatively for adult THA. 34 In the current study, the only association of transfusion with SSI was an increased risk of superficial infection with large volume transfusion in the NM group; this association was not significant. The rarity of SSI in pediatric surgical populations likely limits the likelihood of finding any association.…”
Section: Discussioncontrasting
confidence: 58%
“…The use of autologous blood transfusion for elective orthopaedic surgery is decreasing, despite an overall upward trend in transfusion rates driven by an increase in allogeneic transfusions [7,45]. The decrease in this practice may be attributable to growing concerns regarding its cost-effectiveness and utility in patients without anemia [4,6,18,20], the possibility of iatrogenic anemia leading to increased overall transfusion rates [9,12,19], and some reports suggesting no differences regarding postoperative mortality and infection compared with allogeneic transfusions [9,30]. It therefore is possible that patients of higher socioeconomic status are asking for preoperative donation of blood to their own detriment, and, paradoxically, disadvantaged populations may not be receiving substandard care.…”
Section: Discussionmentioning
confidence: 99%
“…The ASA classification system has been shown to be correlated with multiple factors that increase surgical resource utilization including infection [21], reoperations [22], intraoperative blood loss [23], and duration of surgery [24]. Similarly, hip fracture patients with a greater number of comorbidities have been shown to be more likely to suffer postoperative complications that would require diagnostics and imaging [25], which would explain the increase in radiology charges with ASA score.…”
Section: Discussionmentioning
confidence: 99%